Elevated surface plasmon resonance sensing sensitivity of Au-covered silica sphere monolayer prepared by Langmuir-Blodgett coating - Choi, Baeck B.; Kim, Bethy; Chen, Yiqi; Yoo, Sung Jong; Cho, Younghyun; Jiang, Peng (한국공업화학회, 2021)
The colloidal Langmuir-Blodgett coating process is used to fabricate Au-covered silica sphere monolayer (Au film over silica nanosphere (AuFON)) and study the effects of silica diameter on surface plasmon resonance (SPR) sensing sensitivity. The resulting hexagonal close-packed (HCP) monolayers are prepared with silica sphere diameters of 200, 400, 700, and 1000 nm. In SPR sensing applications, the optical properties of Au-covered silica sphere monolayer are evaluated by measuring normal-incidence reflection spectra and sensing tests. The high sensitivity (nm/RIU) is observed in silica sphere diameter (1000 > 700 > 400 > 200 nm) and plasmon mode (dipole > Fano resonance (FR) > and high order) while the highest sensitivity is 968 nm/RIU (dipole mode, 1000 nm of silica sphere diameter). 3-D Finite Difference Time Domain (FDTD) simulation shows a sensitivity trend similar to the experimental results. (c) 2021 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.